The Academic Development of Education Faculty: Looking Back, Looking Ahead - Wimmer, Randolph; da Costa, José (Alberta Journal of Educational Research, 2007)
A 2003 study about the lives of retired leaders in teacher education reminds us of the significant role that others play in the academic development of professors of education. That study also reveals significant changes in the nature of our work as teacher educators. The authors stress the need for universities to pay greater attention to the academic development needs of beginning teacher educators. Although many research-based universities offer programs for beginning faculty, the focus appears to be on teaching effectiveness. The authors make the case that beginning professors of education are different from those of beginning faculty in other disciplines. An argument is made that many beginning education professors need less support in teaching and service and more in the area of research.